The influence of infant sleep problems and sleep training on maternal subjective well-being - Jacomien Muller; Tharina Guse (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2024)
Background: Disturbed sleep during infancy and early childhood can have a detrimental effect on parental sleep and consequently parental well-being. However, there is a paucity of research on how perceived child sleep problems and behavioural sleep interventions as treatment influence maternal subjective well-being.